The relationship between training status and intensity on muscle activation and relative submaximal lifting capacity during the back squat - Pick, J.; Becque, D. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to compare the relative activation of the vastus lateralis (VL) and vastus medialis (VM) muscles among subjects of different training statuses during the completion of a single set of the back squat performed until failure (SSTF) at an intensity of 85% of the 1 repetition maximum (1RM). Nine trained (TR) and 7 untrained (UT) subjects performed 2 1RM tests followed by an SSTF at 85% of the 1RM on 3 separate days. Activation of VL and VM was recorded using surface electrodes during both the 1RM and SSTF. The data were digitally filtered, rectified, and integrated (IEMG) for the 1RM and each repetition of the SSTF. The SSTF IEMGs were expressed as a percentage of 1RM IEMG (%1RM IEMG) for the first repetition, as well as 40, 60, 80, and 100% of the repetitions completed in the SSTF. The TR was significantly stronger than UT in 1RM back squat strength. The TR and UT exhibited similar VL activation. The TR had significantly greater activation for VM than UT. The combined activation (COMB) of these 2 muscles revealed significantly greater muscle activation by TR than UT. The TR used a significantly greater %1RM IEMG at 40, 80, and 100% of completed repetitions for VL. The %1RM IEMG for TR was also significantly greater at 80 and 100% of the completed repetitions for VM. The COMB %1RM IEMG for TR was significantly greater than that of UT at 80 and 100% of completed reps. The TR completed significantly more repetitions (9.67 ± 0.91 repetitions) than UT (7.14 ± 0.74 repetitions) in the SSTF. The results indicate that TR can utilize a greater %1RM IEMG. This may contribute to an increase in relative submaximal lifting capacity and invalidate the method of defining training intensity utilizing a percentage of the 1RM for a specific number of repetitions.